2023
DOI: 10.1126/sciadv.ade9023
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of peptidoglycan synthesis is sufficient for total arrest of staphylococcal cell division

Abstract: Bacterial cell wall biosynthesis is the target of many important antibiotics. Its spatiotemporal organization is closely coordinated with cell division. However, the role of peptidoglycan synthesis within cell division is not fully understood. Even less is known about the impact of antibiotics on the coordination of these two essential processes. Visualizing the essential cell division protein FtsZ and other key proteins in Staphylococcus aureus , we show that antibiotics targeting pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…6a,b; Supplementary Table 3; Supplementary Movie 5). Strikingly, treatment of cells with the glycopeptide antibiotic vancomycin that inhibits PG synthesis, previously shown to cause a total arrest of cell division at all stages in S. aureus within minutes 32 , nearly completely stopped the directional movement of FtsW-HT and HT-DivIB (Supplementary Fig. 10; Supplementary Movie 5).…”
Section: Pg Synthesis By Ftsw/pbp1 Drives the Directional Movement Of...mentioning
confidence: 92%
See 1 more Smart Citation
“…6a,b; Supplementary Table 3; Supplementary Movie 5). Strikingly, treatment of cells with the glycopeptide antibiotic vancomycin that inhibits PG synthesis, previously shown to cause a total arrest of cell division at all stages in S. aureus within minutes 32 , nearly completely stopped the directional movement of FtsW-HT and HT-DivIB (Supplementary Fig. 10; Supplementary Movie 5).…”
Section: Pg Synthesis By Ftsw/pbp1 Drives the Directional Movement Of...mentioning
confidence: 92%
“…Previous data have shown that the cell division process in S. aureus depends on PG synthesis at all stages, as its inhibition by vancomycin is sufficient for a total arrest of septum constriction 32 . Based on these observations, we hypothesized that the rates of septal PG synthesis and septum constriction may correlate.…”
Section: Pg Synthesis By Ftsw/pbp1 Drives the Directional Movement Of...mentioning
confidence: 98%
“…Most antimicrobials interfering with the lipid II biosynthetic cycle such as vancomycin, ramoplanin and teixobactin, cause a breakdown of the cell division and membrane coordinated cell wall biosynthetic machineries . These antibacterial agents block cell wall synthesis by binding lipid II with high affinity, thereby preventing transglycosylation and transpeptidation reactions .…”
Section: Resultsmentioning
confidence: 99%
“…6,10 Most antimicrobials interfering with the lipid II biosynthetic cycle such as vancomycin, 27 ramoplanin 28 and teixobactin, 29 cause a breakdown of the cell division and membrane coordinated cell wall biosynthetic machineries. 30 These antibacterial agents block cell wall synthesis by binding lipid II with high affinity, thereby preventing transglycosylation and transpeptidation reactions. 9 Since 5c or 5f did not impede the PBP2-catalyzed transglycosylation reaction step of cell wall synthesis in vitro at 2-fold (Figure S2) as well as 4-fold molar ratio (result not shown) of bisindoles with respect to lipid II, we next sought to determine whether bisindoles interfere with a late-stage membrane-associated PGN biosynthesis step.…”
Section: Synthesis Of N-deprotected Bisindolesmentioning
confidence: 99%
“…We propose that mislocalization of FtsW may contribute to lipid II reduction during phage infection. Since the biosynthesis of the bacterial cell wall is closely coordinated with cell division ( 48 , 53 ), we hypothesized that this could be a viable strategy for phages to influence PG synthesis during cell division and to lyse their host, which has been observed in E. coli ( 39 , 54 ).…”
Section: Discussionmentioning
confidence: 99%